Factors affecting responsibility accounting and its impact on management performance of textile and garment enterprises in Vietnam - Lan Anh Dang (Cogent Business & Management, 2024)
This study aims to investigate the factors influencing Responsibility Accounting and its impact on the Management Performance of textile and garment enterprises in Vietnam. Utilizing both qualitative and quantitative research methods, the study surveyed employees and managers from the accounting departments of large-scale textile and garment enterprises in Vietnam. The qualitative research involved summarizing the business conditions of these enterprises, developing research models and hypotheses based on a literature review, and gathering comments from managers and accountants on the questionnaire's quality. The quantitative research involved using SPSS and AMOS tools to measure, analyze, and interpret the relationships between factors in the model. The results of the linear structural model show that factors including management decentralization, managers' perspective on Responsibility Accounting, accounting staff qualifications, and information technology application qualifications have the same impact on Responsibility Accounting implementation in textile and garment enterprises in Vietnam. This study also proves that Responsibility Accounting has a positive impact on the Management Performance of the companies. At the same time, research also shows that the higher the effectiveness of Responsibility Accounting, the higher the management skills, financial efficiency and the effectiveness of management activities in these businesses. Based on these discoveries, the author suggests recommendations for both the government and businesses to enhance the effectiveness of Responsibility Accounting, thus boosting their Management Performance.
Keywords: 650; Responsibility accounting; management performance; textile and garment enterprises; Vietnam